A ocorrência de lagartos marinhos (Mosasauridade: Lepidosauria) e sua associação faunística no cretáceo da bacia Pernambuco - Paraíba, Nordeste do Brasil - Carvalho, Luciana Barbosa de (1996)
This dissertation carries out a survey of the occurrences of the mosasaurid marine lizard fauna from the Pernambuco-Paraíba basin of the Northeastern Brazil. Specimens housed in paleontological collections from several institutions have been examined and new material from the mentioned basin has been collected. The specimens are described and compared and a new taxonomic proposal is presented. Based on two field trips to the mentioned area, the stratigraphic and geochronologic occurrences of mosasaurs in the Pernambuco-Paraíba basin could be confirmed, updated, and revised. Furthermore, a better understanding of the paleofaunistic association of those creatures was obtained. This study recovers, expands, and complements the limited information so far available in the literature about the Brazilian mosasaurid taxóns. The sedimentary strata containing the studied fauna are characterized and a summary of the information available in the scientific literature is presented, including new data obtained during the field work. Geopaleontological aspects concerning the limit between the Cretaceous and the Tertiary (KT boundary), which is of relevant scientific importance for the evolutionary history of the mosasaurids, are discussed. Since there is no publication available in the Portuguese language that presents a synthesis regarding mosasaurs, the present study includes several morpholological and anatomical information, and discusses several aspects regarding the evolution and the palaeoecological relations of this group. A list of the most important outcrops cited in the literature and the ones studied by the author during the field work are presented, including lithostratigraphic, paleontological, and locality information. The geographic coordinates of the outcrops have been obtained using GPS, providing a more precise locality data than the ones available so far in the literature.